2022
DOI: 10.1111/bjso.12542
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the places of young people in public space: Conflict, belonging and identity

Abstract: Building on the growing discursive approach to peopleplace relations, we examine how young people negotiate people-place tensions and relations, and how they establish their everyday sense of place in contemporary public spaces.Facilitated by the use of Collaborative Spatial Mapping, analysis of focus group data from 51 young people focuses on three aspects of participants' talk about the places that make up their everyday lives: appropriation of microgeographical spaces, the construction of autobiographical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
2
6
0
Order By: Relevance
“…Also, in line with other social‐psychological studies, analysis indicated that different representations of integration and belonging, drawn on different spatial scales and local/urban views of citizenship positioned participants in the in‐between temporality of belongingness in (differently constituted) communities (Gray & Manning, 2014, 2022; Dixon et al, 2006, 2022; Hopkins & Dixon, 2006). Furthermore, accounts of relationships with the environment re‐shaped participants' ‘private’ experience of places as much as they produced particular social, moral and even political effects (Di Masso et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Also, in line with other social‐psychological studies, analysis indicated that different representations of integration and belonging, drawn on different spatial scales and local/urban views of citizenship positioned participants in the in‐between temporality of belongingness in (differently constituted) communities (Gray & Manning, 2014, 2022; Dixon et al, 2006, 2022; Hopkins & Dixon, 2006). Furthermore, accounts of relationships with the environment re‐shaped participants' ‘private’ experience of places as much as they produced particular social, moral and even political effects (Di Masso et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…In the last two decades, social psychology has been influenced by the ‘spatial turn’ in social sciences, considering spatial aspects as important constituents of everyday life and intergroup relations (Di Masso et al, 2014, 2021; Dixon & Durrheim, 2004; Manzo, 2014). Authors have stressed that spatial practices and space as a discursive resource involve particular ways of constituting people–environment relations with important political and ideological implications and with (often) exclusionary outcomes (Di Masso, 2015; Di Masso et al, 2011, 2017; Dixon et al, 2006; Gray & Manning, 2014, 2022). Research has indicated that the spatial dimensions of group contact, including physical and symbolic boundaries, as well as the management of spatial resources (Di Masso, 2015; Durrheim & Dixon, 2001, 2005) can serve to (de)legitimize people's presence (Kirkwood et al, 2013) and to (re)produce a specific socio‐spatial moral order (Stokoe & Wallwork, 2003; McCabe & Stokoe, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned constructions of city spaces were related to different subject positions and presupposed different citizenship constructions and claims. Despite their often precarious positioning within urban spaces and in line with the findings of other social and political psychology studies on spatial relations (Di Masso, 2012;Dixon et al, 2006;Gray & Manning, 2014Ropert & Di Masso, 2021), our findings show that through place attachment and place-making strategies, participants engaged in locational forms of citizenship and developed a sense of belongingness to city spaces (Gray & Manning, 2022). In particular, acts of urban citizenship were related to the right to be part of specific multiethnic communities and to deploy strategies that dismantle established spatial hierarchies, such as renaming areas or deploying everyday activities (Extracts 1 and 2).…”
Section: Conc Lusionssupporting
confidence: 86%
“…In line with what is often referred to as the spatial turn in psychology, social psychology has increasingly engaged with the importance of place for human lives (e.g. Dixon & Durrheim, 2000; Dixon et al., 2006; Gray & Manning, 2014, 2022; Hodgetts et al., 2010; Hopkins & Dixon, 2006; Stokoe & Wallwork, 2003; Toolis, 2017; Toolis & Hammack, 2015a, 2015b). Locational citizenship speaks to the right to have a place in public space, with the associated acceptance, recognition and positive belonging related to legitimate presence in such public spheres (Di Masso, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…There is some psychological work focused specifically on children in public places and children's use of space (e.g. Gray and Manning, 2014, 2022; Lim & Barton, 2010; Min & Lee, 2006). In psychology, less is known related to recognition and acceptance of the use of space tied to particularly marginalized groups, such as street children.…”
Section: Street Childrenmentioning
confidence: 99%